PILGRIM PRAYER LAW BASED ON THE PERSPECTIVE OF MUHAMMADIYAH LEADERS IN ENREKANG REGENCY, SOUTH SULAWESI - Erfandi, Erfandi; Abbas, Abbas; Hijazi, Muhammad Chiar; Anshar, Anshar; Misran, Misran (Journal of Family Law and Islamic Court, 2022)
Research on Pilgrim Prayer Law Based on the Perspective of Muhammadiyah Leaders  in Enrekang Regency,  South Sulawesi is Qualitative.  As stated in the formulation of the problem, in addition to researching the Pilgrim Prayer Law Based on the Perspective of the Muhammadiyah Leadership in  Enrekang Regency, the researcher also examined the Pilgrim Prayer Law Based on the  Perspective of  the Imams of the four schools, namely the Hanafi School, the Maliki School, the Shafi'i School and the Hanbali School  .  This study  aims to find out the  extent of the  perspectives of  the Muhammadiyah Leadership  and the  Imam of the Four Schools on the law of pilgrim prayer.   This is in order to  increase understanding, both  among   intellectuals and among the layman.  The results of  this study show that the scholars of the four  schools have different opinions about   the law of  prayer of pilgrims.   Imam Abu Hanifah An- Nu'man bin Tsabit stated that the pilgrim's prayer was the sunnah of mu'akkadah.  Imam Malik bin Anas stated that the law of pilgrim prayer is the sunnah of mu'akkadah. Imam Muhammad ibn Idris As-Shafi'i stated that the pilgrim's prayer was fardhu kifayah.  Imam Ahmad ibn Hanbal stated that the law of  pilgrim prayer is mandatory.  As for the  perspective of the Muhammadiyah Regional Leader (PDM), Enrekang Regency stated that the pilgrim's  prayer is fardhu kifayah.  This opinion is in harmony with the  opinion of  Imam Shafi'i and is also in harmony with the tarjih   of muhammadiyah.--Penelitian tentang Hukum Shalat Jamaah Berdasarkan Perspektif Pimpinan Muhammadiyah di Kabupaten Enrekang Sulawesi Selatan bersifat Kualitatif. Sebagaimana yang tertera pada rumusan masalah, selain meneliti tentang Hukum Shalat Jamaah Berdasarkan Perspektif Pimpinan Muhammadiyah di Kabupaten Enrekang, peneliti juga meneliti Hukum Shalat Jamaah Berdasarkan Perspektif imam empat mazhab, yaitu Mazhab Hanafi, Mazhab Maliki, Mazhab Syafi’i dan Mazhab Hanbali. Penelitian ini bertujuan untuk mengetahui sejauh mana perspektif Pimpinan Muhammadiyah dan Imam Empat Mazhab tentang hukum shalat jamaah ini. Hal ini agar dapat menambah pemahaman, baik itu di kalangan intelektual maupun di kalangan awam. Hasil dari penelitian ini menunjukkan bahwa ulama empat mazhab berbeda pendapat tentang hukum shalat jamaah ini. Imam Abu Hanifah An- Nu’man bin Tsabit menyatakan bahwa shalat jamaah hukumnya adalah sunnah mu’akkadah. Imam Malik bin Anas menyatakan bahwa hukum shalat jamaah adalah sunnah mu’akkadah. Imam Muhammad bin Idris As-Syafi’i menyatakan bahwa shalat jamaah hukumnya adalah fardhu kifayah. Imam Ahmad bin Hanbal menyatakan bahwa hukum shalat jamaah adalah wajib. Adapun mengenai perspektif Pimpinan Daerah Muhammadiyah (PDM) Kab. Enrekang menyatakan bahwa shalat jamaah hukumnya adalah fardhu kifayah. Pendapat ini selaras dengan pendapat Imam Syafi’i dan juga selaras dengan tarjih muhammadiyah.